2022
DOI: 10.26634/jet.19.2.19010
|View full text |Cite
|
Sign up to set email alerts
|

“EFL teachers” TPACK self-efficacy beliefs, web 2.0 competence and perceptions towards web 2.0 tools

Abstract: The recent advancement of digital technologies has triggered a prominent shift within the field of language education. Considering the teachers' vital roles in adopting modern instructional technologies, this study investigates in-service EFL teachers' TPACK self-efficacy levels, explores the relationship between their TPACK self-efficacy levels and their demographic features and perceptions towards Web 2.0 technologies. Employing a mixed method design, the study collected quantitative and qualitative data in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…But some researchers found that digital competence does not influence self-efficacy [46][47][48]. Fewer studies focus on self-efficacy and digital tools use during ICT integration and propose there is a significant influence on teachers' self-efficacy and digital tools use [49,50]. Additionally, some studies suggested there is no difference between teachers' age, gender, teaching experience, and self-efficacy during ICT integration [7,51].…”
Section: Teachers' Self-efficacy and Ict Integrationmentioning
confidence: 99%
“…But some researchers found that digital competence does not influence self-efficacy [46][47][48]. Fewer studies focus on self-efficacy and digital tools use during ICT integration and propose there is a significant influence on teachers' self-efficacy and digital tools use [49,50]. Additionally, some studies suggested there is no difference between teachers' age, gender, teaching experience, and self-efficacy during ICT integration [7,51].…”
Section: Teachers' Self-efficacy and Ict Integrationmentioning
confidence: 99%